Konsep Puasa dalam Islam: Analisis Hukum dan Dimensi Spiritual - Edi Hermanto; Farhan Aiman Rafa’el; Hasbullah Hasbullah; Harpan Harahap (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This article discusses the meaning and regulations of fasting in Islam as one of the fundamental acts of worship that encompasses theological, spiritual, moral, and social dimensions. The purpose of this study is to explain the definition of fasting from both linguistic and Islamic legal perspectives, to examine its legal foundations, and to describe the laws and types of fasting within the framework of Islamic jurisprudence. The method employed is library research, drawing upon the Qur’an, the traditions of the Prophet Muhammad ﷺ, scholarly consensus (ijma‘), as well as classical and contemporary works of Islamic jurisprudence. The findings indicate that etymologically, fasting means self-restraint, while terminologically it is defined as refraining from all acts that invalidate fasting from dawn until sunset with sincere intention for the sake of Allah. The legal basis of fasting is clearly established in Surah Al-Baqarah verses 183–185, the hadith concerning the pillars of Islam, and the consensus of Muslim scholars regarding the obligation of fasting during the month of Ramadan. This study further explains that fasting is classified into several categories, including obligatory fasting such as Ramadan, qadha, expiation (kafarat), and vows (nazar); recommended fasting such as Mondays and Thursdays, Ayyamul Bidh, Arafah, and Ashura; as well as fasting that is prohibited or disliked at certain times. Substantively, fasting functions as a means of fostering piety, controlling desires, purifying the soul, and cultivating social empathy. Thus, fasting is not merely a ritual practice but also plays a significant role in shaping personal character and maintaining balance in a Muslim’s life. The implications of this study are expected to serve as an academic reference for students and researchers in understanding fasting comprehensively and applying its values in religious and social life based on Islamic principles and social ethics.